2008
DOI: 10.1007/s10151-008-0404-z
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the ileocaecal valve

Abstract: The ileocaecal valve can cause concern when it is enlarged. We define the normal and abnormal appearances of the ileocaecal valve and illustrate the importance of using CT and endoscopy to make the correct diagnosis, avoiding any further unnecessary interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Of note, the symptoms were independent of the size of the lesion, which may add to the difficulty of diagnosis 1. The advent of two-dimensional CT scan has enabled non-invasive evaluation of the ICV and more precise diagnosis of colonic fatty lesions 15. The findings of submucosal fats should however be interpreted cautiously in conjunction with the endoscopic results and clinical symptoms, as the mere presence of submucosal fatty infiltration of the valve is considered a normal variant.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the symptoms were independent of the size of the lesion, which may add to the difficulty of diagnosis 1. The advent of two-dimensional CT scan has enabled non-invasive evaluation of the ICV and more precise diagnosis of colonic fatty lesions 15. The findings of submucosal fats should however be interpreted cautiously in conjunction with the endoscopic results and clinical symptoms, as the mere presence of submucosal fatty infiltration of the valve is considered a normal variant.…”
Section: Discussionmentioning
confidence: 99%
“…In 90% of cases the terminal ileum enters through the medial wall of the caecum, which is the dependent area in the left lateral (LL) position. It has been reported that while the patient is in the LL position, the medial wall of the caecum is dependent, and in most instances, the terminal ileum opens into this area [ 23 ]. When stool obscures this area, it becomes difficult to visualise the entire caecum.…”
Section: Introductionmentioning
confidence: 99%